Yield trends of temperate cereals in high latitude countries from 1940 to 1998 - Slafer, Gustavo A.; Peltonen-Sainio, Pirjo (MTT Agrifood Research Finland, 2001)
Buenos Airesin yliopisto, Argentiina ja MTT (Maa- ja elintarviketalouden tutkimuskeskus) Vehnä on ainoa lauhkean vyöhykkeen vilja, jonka satoisuuden kehitystä on aiemmin tarkasteltu kattavasti maailmanlaajuisesti ja viljelyalueittain. Tämän tutkimuksen tarkoituksena oli verrata kauran, ohran, rukiin ja vehnän satoisuuden kehittymistä viimeisen viiden vuosikymmenen ajan erityisesti pohjoisen viljelyn alueilla (Kanada, Norja, Ruotsi, Suomi ja Tanska). Lisäksi arvioitiin kasvinjalostuksen osuutta satoisuuden kehittymisessä. Aineistona käytettiin FAO:n tilastoja. Kun verrattiin eri viljalajien satoisuuden muutoksia tutkitulla ajanjaksolla (1950-1998), havaittiin, että rukiin hehtaarisadot kasvoivat tasaisesti noin 28 kg vuodessa. Sen sijaan ohran (38 kg/ha/vuosi) ja kauran sadot (32 kg/ha/vuosi) kasvoivat ensin huomattavasti 1970-luvun paikkeille saakka, ja kasvu tasaantui voimakkaasti viimeisen 30 vuoden aikana. Myös vehnän satoisuuden kehitystä kuvasi parhaiten bi-lineaarinen malli: vähäistä satoisuuden kasvua 1960-luvulle saakka, satoisuuden kolminkertaistuminen 1990-luvulle mentäessä ja tästä edelleen kasvun tasaantuminen. Tutkittaessa satoisuuskehitystä niin pohjoismaissa kuin Kanadassakin voitiin havaita, että yleisesti ottaen vehnän satoisuus kehittyi muita viljoja nopeammin. Tämä kuvastanee vehnän arvostusta ja kehitystyöhön käytettyjen tutkimusvarojen runsautta. Toisaalta kauran ja ohran, mutta vähissä määrin myös vehnän, osalta voidaan havaita satoisuuskehityksen hidastumista viime vuosikymmenenä. Alustavat tuloksemme antoivat myös viitettä siitä, että kasvinjalostuksen rooli tutkittujen viljalajien satoisuuden parantamisessa oli pohjoisilla viljelyalueilla pienempi (poikkeuksena vehnän tuotanto Kanadassa) kuin mitä on raportoitu viljeltäessä vehnää ja ohraa alhaisemmilla leveysasteilla.

Wheat is the only temperate cereal for which yield trends have been exhaustively analysed on both global and national bases. This paper aims (i) to compare global yield trends of wheat, barley, oat and rye for the last five decades, (ii) to analyse their yield trends in Canada, Denmark, Norway, Sweden and Finland, the northernmost limits for extensive agriculture, and (iii) using case studies, to assess the relative contribution to yield gains made by cereal breeding. Average global yield data from FAO were regressed against years using linear or bilinear regressions. Yield gains in absolute and relative terms were calculated for comparison among countries and cereals. Data from the literature were used to assess the estimated contributions made by breeding to yield gains. Global yield trends were not standard throughout the 1950-1998 period: rye exhibited a constant yield gain (c. 28 kg ha-1 y-1), while barley and oat showed marked increases until around 1970 (c. 38 and 32 kg ha-1 y-1, respectively) but quite modest increases (c.19 and 5 kg ha-1 y-1, respectively) over the last 30 years. Wheat also showed a bilinear trend with only limited yield gains until the 1960s, followed by a more than 3-fold increase in rate of yield gain from then on (16 and 40 kg ha-1 y-1, respectively). However, during the 1990s wheat yield gains have been less than previously. Hence, global yields of barley, oat and wheat have increased very slowly lately. Trends for each combination of cereals and countries indicated consistently higher yields during the 1990s than at mid-century. In general, wheat yield tended to increase at a faster rate than yield of the other cereals. There was a trend in the last decade of low rates of yield increase compared with those of previous decades. This was clear for oat and barley, and a similar trend is emerging for wheat. This suggests that genetic and/or management improvements have had less effect in recent times. Furthermore, we found preliminary evidence to suggest that with the exception of wheat in Canada, genetic contributions in northern areas were smaller than those reported for wheat and barley at lower latitudes. Therefore, alternative approaches must be sought for future breeding work under these high latitude conditions.
Keywords: Ka; kaura; ruis; ohra; vehnä; sato; barley; breeding; northern agriculture; oat; rye; wheat; yield